Single shot emittance measurement from beam size measurement in a drift section - Thomas, C; Rehm, G; Bartolini, R; Delerue, N; Bajlekov, S (2010)
Single shot emittance measurement is essential to assess the performance of new generation light sources such as linac based X-ray FELs or laser plasma wakefield accelerators. To this end, we have developed a single shot transverse emittance measurement using at least 4 screens inserted in the beam at the same time, measuring the beam size at different positions in a drift space in one shot. We present here test measurements performed at Diamond in the transfer line from the Booster to the Storage Ring, using thin OTR screens. Additionally, we compare these measurements with results from the more conventional quadrupole scan method. The validity and limits of the new method are also discussed.